Designing Large Housing Estate for Sustainable Communities - Hofbauer, Christian Kersten; Madadi-Kandjani, Elham (Journal of Environmental Accounting and Management, 2026)
There is no doubt that large housing estate has an important impact on community design of sustainable neighborhoods and on the ur- ban and regional housing markets of most cities in Europe. During the post war period main issue was a high quality and well equipped housing with a hopeful perspective and glorious and idealistic ideas. In the last decade most of the designers and planners have improved their planning strategies for empowering the environmental, social, cultural, and economic impact of their designs. Sustainable design for nowadays and future generation and new planning policies are the most important factors in new planning processes. This research aims at investigating if sustainable large housing development can form strong communities in which residents enjoy high quality of design and life and environmental friendly neighborhoods. The re- search findings suggest that a sustainable urban development seems to be essential to a sustainable large housing development. The re- sults of the research show that physical environment in line with nature, cultural background, the sustainable use of space, and af-fordable dwelling leads to a worth living community design.